Exercise addiction in individuals who exercise regularly - Bekir Furkan Tüzer; Havva Demirel (Physical Education of Students, 2024)
Background and Study Aim. Addiction has significant effects on individuals who exercise regularly, influenced by factors such as age and gender. This study aimed to measure the exercise addiction levels among university students who regularly engage in fitness activities.